Cover Crops Could Offset Crop Residue Removal Effects on Soil Carbon and Other Properties: A Review. (1st September 2017) - Ruis, Sabrina J.; Blanco‐Canqui, Humberto
Abstract : Core Ideas: Corn residue removal reduces soil organic C stocks and other soil properties. Cover crop increases soil organic C stocks and other properties. Cover crop may not offset soil organic C losses from residue removal in the short term. More data are needed on cover crop effects on soil properties after residue removal. Crop residue removal for livestock or biofuel production is common. Excessive residue removal may reduce soil organic carbon (SOC) and other soil properties. Cover crop (CC) could be a strategy to ameliorate negative effects of residue removal, but this has not been widely discussed. We synthesized studies on the impacts of CC addition following crop residue removal on SOC and related properties, discussed opportunities and challenges of using CC after residue removal, and highlighted research needs. We first briefly reviewed the separate effects of residue removal and CC before reviewing their combined effects. Our review found that ≥50% residue removal reduced SOC stocks by 0.87 Mg ha −1 yr −1 and <50% removal by 0.31 Mg ha −1 yr −1 . However, CC increased SOC by 0.49 Mg ha −1 yr −1, suggesting that CC could offset at least part of the SOC lost with removal. Studies evaluating CC effects on soil properties after residue removal are few and short term (<6 yr) but appeared to show limited potential of CC to offset residue removal effects. However, some studies indicated trends for increased SOC, suggesting CC may offset removal effects in the long term. While opportunities exist to integrate residue removal with CC use, challenges including low CC biomass and reduction in crop yield in water‐limited regions must be addressed. Further research on interactive effects of CC and residue removal is needed across different cropping systems and climates.